Topical antibiotics for acute rhinosinusitis in children - Denis A. Tulupov; Elena P. Karpova (Медицинский совет, 2021)
Rhinitis or nasopharyngitis are the most common manifestations of acute respiratory viral infection (ARVI) in children. Inflammation of the mucous membrane in the nasal cavity develops in more than 70% of ARVI cases, and rhinovirus infection is the most common etiological factor for these conditions. In this article, the authors present a short review of the existing data on the use of combined drugs based on N-acetylcysteine and tuamingheptan in the treatment of acute rhinological pathology in children. The authors present generalized data on the nature of the course of acute rhinitis, as the main manifestation of acute respiratory viral infection in children, and modern views on the tactics of treating this condition. The main theses on symptomatic treatment of nasal obstruction in acute rhinitis using nasal decongestants are presented. However, the use of nasal vasoconstrictor drugs as monotherapy to treat acute rhinitis may be less effective, as a buildup of thick discharge in the nasal cavity, which a patient is not always able to blow out from the nose (especially in childhood), prevents the drug injected into the nasal cavity from contacting the mucous membrane. The main pathogenetic grounds for the use of mucolytics in the treatment of acute rhinitis and acute rhinosinusitis are presented. The use of N-acetylcysteine-based drugs in otorhinolaryngological practice has been substantiated. N-acetylcysteine is a direct mucolytic agent. Its action is associated with the ability of its free sulfhydryl groups to break intra- and intermolecular disulfide bonds of acidic mucopolysaccharides of a thick discharge. As conclusions, the authors talk about the prospect of using combined drugs based on N-acetylcysteine and tuamingheptan both in the symptomatic treatment of acute rhinitis and as an adjunct treatment for acute rhinosinusitis in children.